(untitled) (Revista Rupturas, 2016)
We criticize the concept of NEET (not in education, employment or training) using the results of the first Survey of Time Use in the Greater Metropolitan Area of Costa Rica of 2011. The objective is to use time as an indicator to express gaps and inequalities on the distribution, use, exchange, and value of time, that determine consequently the organization of everyday life on the population between 12 and 35 years old, who does not attend formal education and is neither employed.